The theoretical framework of transformational and transactional leadership styles in enhancing job satisfaction of nurse educators in Malaysia - Moey, Soo Foon (Research Publish Journals, 2016)
Some conclusions from leadership models indicated that personality traits, the situation, leader member relations and power influence the practice of leadership. Two theories; the Hagedorn Theory of Job Satisfaction (2000) and Bakker and Demerouti Job Demands-Resources (JD-R) Theory (2007) together with Bass and Avolio (2004) Full Range Leadership Model make up the theoretical frame of the study. The importance of the transformational and transactional leadership styles in determining the nature of work environment is well documented and is of increasing significance to the retention of nurse educators. Leaders that engage in transformational leadership style and the contingent reward attribute of transactional leadership style tend to increase the value and significance of their work, resulting in subordinates to be intrinsically motivated via the perceptions of well-being. Engaged subordinates often display a deep positive emotional connection with their work, are likely to go the extra mile to achieve organizational accomplishments.The theoretical framework assumes that transformational and transactional leadership-work place engagement is indirect and impacted through the mechanism of perceived subordinates’ well-being, ultimately leading to job satisfaction.